Reconstructing ethical artificial intelligence use among university students based on islamic values - Abdussyukur; Mohammad Akmal Haris; Ramadana Ramadana; Enny Haryanti; Nuraini Muhammad Daud; Yunita Abdullah Aji (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
This study investigates the ethical implications of Artificial Intelligence (AI) usage among university students and reconstructs a value-based ethical framework grounded in Islamic moral epistemology. The rapid integration of AI into academic practices has transformed how students engage with knowledge, raising critical concerns regarding authorship, academic integrity, and moral responsibility. This research adopts a qualitative interpretivist design to explore students’ experiences, ethical reasoning, and behavioral patterns in using AI within an اسلامی higher education context. Data were collected through semi-structured interviews, observations, and document analysis involving students and lecturers, and analyzed using a rigorous thematic approach. The findings reveal that AI has become an integral cognitive partner in academic work, enhancing efficiency while simultaneously reducing epistemic ownership and depth of understanding. More critically, the study identifies a persistent ethical ambiguity, where students struggle to distinguish acceptable AI use from academic misconduct, largely due to blurred authorship and the absence of clear institutional guidelines. The results further demonstrate a significant disconnection between students’ awareness of Islamic ethical values and their actual digital practices, indicating a contextual gap in moral application. In response, this study develops a reconstructed ethical framework that translates core Islamic values—honesty, trustworthiness, responsibility, and justice—into practical guidelines for AI usage. Theoretically, this research contributes by extending AI ethics discourse beyond Western paradigms and integrating spiritual and moral dimensions into digital ethics. Practically, it offers a foundation for designing ethically grounded policies and pedagogical strategies in higher education. Ultimately, the study argues that sustainable AI integration depends on aligning technological advancement with deeply internalized ethical consciousness